Efficiency and Profitability Analysis of Agricultural Cooperatives in Mpumalanga, South Africa - Xaba, Thembi; Marwa, Nyankomo; Mathur-Helm, Babita (Journal of Economics and Behavioral Studies, 2018)
Agricultural cooperatives are expected to generate sustainable profit as they are established as a vehicle of economic development. Efficiency and profitability analysis measures the performance of a firm, and assists management in decision-making through benchmarking with other firms (Marwa & Aziakpono, 2014). To understand the performance of agricultural cooperatives, our study analysed efficiency and profitability using an efficiency-profitability matrix to provide for multi-dimensional analysis. The study used secondary data from annual financial statements for the financial years 2015/16 collected from 19 agricultural cooperatives. Technical efficiency was estimated using Data Envelopment Analysis (DEA) and profitability was estimated using Returns on Assets (ROA). The median scores were 68% for technical efficiency and 10% for profitability. Using the 68% efficiency and 10% profitability benchmark, the matrix separated best performers from low performers. The matrix indicated that 26% of the cooperatives had high-efficiency levels with high profitability (stars), however there was an even distribution between the stars and sleepers: 5 out of 19 cooperatives were sleepers and 5 out of 19 were stars. The majority of the decision-making units (DMUs) at 42% (8 out of 19) are in quadrant 3, categorised as ‘question mark’. These DMUs had low-efficiency scores and low profitability ratios. Only 1 out of 19 cooperatives had high-efficiency levels and low profitability scores. The results demonstrate that technically efficient firms do not always translate to profitable firms: in this regard, management needs to investigate how best to allocate resources in order to remain relevant within the business context and competition. Policy makers need to investigate other drivers of efficiency and profitability when measuring the performance of a firm to influence future policy directives.